Synthesis of the Heptasaccharide Repeating Unit of the Cell Wall O‐Polysaccharide of Enterotoxigenic Escherichia coli O139. Issue 1 (12th August 2015) - Ghosh, Tamashree; Misra, Anup Kumar
Abstract: Enterotoxigenic Escherichia coli (ETEC) like the O139 strain are mostly responsible for traveler's diarrhea and causes diseases in pigs, cattle, and poultry. A convenient synthetic strategy was developed for the synthesis of the heptasaccharide repeating unit of the cell wall lipopolysaccharide of the E. coli O139 strain. The p ‐methoxybenzyl (PMB) group was used as a temporary protecting group which was removed in situ under the glycosylation conditions by changing the reaction temperature during the synthesis of the target compound. All glycosylation steps gave high yields with good stereoselectivity. A (2, 2, 6, 6‐tetramethylpiperidin‐1‐yl)oxyl (TEMPO)‐mediated selective oxidation of the primary hydroxyl group was carried out using a biphasic reaction condition at the late stage of the synthesis. Such synthetic oligosaccharides could later be effectively conjugated with proteins to prepare glycoconjugate derivatives as vaccine candidates. Abstract : Hello heptasaccharide ! Escherichia coli O139 belongs to the enterotoxigenic subgroup mostly responsible for traveler′s diarrhea and some animal intestinal diseases. A heptasaccharide repeating unit of the lipopolysaccharide of E. coli O139 strain has been efficiently synthesized via one‐pot reactions. A p ‐methoxybenzyl (PMB) group was used as a protecting group, and all glycosylation steps gave high yields and good stereoselectivity.